Ulva as a functional feed: a practical investigation into the effects of Ulva lacinulata on the growth, consumption, health and gut microbiota of the farmed abalone Haliotis midae - Brand, Morgan (Department of Biological Sciences, 2024)
Since around 2000, there has been increased adoption of cultivation of the macroalga Ulva by the South African abalone aquaculture industry using IMTA systems. Farms that use fresh Ulva as a supplement to formulated feed have reported a reduction in the volume of formulated feed required to achieve optimal growth of abalone however, there are no standard methods available for integration into production systems. This study shows that IMTA-grown Ulva, or specific components thereof, could be used to reduce the farms reliance on formulated feeds, enhance feed consumption, improve growth rates and product quality, positively influence the immune and metabolic state of abalone while also impacting the gut microbial ecology. The supplementation of formulated feed with fresh IMTA-grown Ulva increased the total daily feed consumption by 90 % and reduced the reliance on formulated feeds by 60 % in a farmscale trial. The basal haemolymph glucose concentration for abalone fed formulated feeds was higher, and demonstrated a significantly prolonged period of hyperglycaemia when compared to abalone fed on fresh Ulva. The immune response of abalone fed formulated feed was not significantly different to that of abalone fed fresh Ulva, however Ulva fed abalone had more pronounced activity from stimulated haemocytes. Feeding fresh Ulva, as a partial replacement (40%) for a formulated feed, significantly improved SGR and MISL compared to that of abalone fed on either diet individually. Abalone that were fed fresh Ulva had significantly lower muscle glycogen content and higher tissue moisture content than abalone fed formulated feed AB or the mixed feeding regime ABFU. The denaturing gradient gel electrophoresis data clearly separated the gut microbial fingerprints into two groups, with one cluster consisting mainly of abalone maintained on formulated feeds and the other cluster comprised of abalone fed fresh Ulva diets. The analysis of specific bands within the DGGE data indicates that abalone fed fresh Ulva diets, and its components, produced significant associations in their intestinal bacterial patterns. Collectively, these findings provide a basis for further investigation into specific roles of extracts obtained from fresh Ulva on the growth, health, physiology and microbiome of aquaculture species.